2006
DOI: 10.1186/1471-2105-7-204
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting trait heterogeneity: a comparison of three clustering methods applied to genotypic data

Abstract: BackgroundTrait heterogeneity, which exists when a trait has been defined with insufficient specificity such that it is actually two or more distinct traits, has been implicated as a confounding factor in traditional statistical genetics of complex human disease. In the absence of detailed phenotypic data collected consistently in combination with genetic data, unsupervised computational methodologies offer the potential for discovering underlying trait heterogeneity. The performance of three such methods – Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 48 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…Therefore, in pharmacogenomics greater emphasis may have to be placed on functional validation of GWAS “signals” and on biological plausibility. Additionally, one must recognize that the larger the sample size, the more likely that features which confound the genotype/phenotype relationship will be undocumented or uncontrolled, thus diluting the “purity” of the phenotype and potentially reducing power [25]. …”
Section: Considerationsmentioning
confidence: 99%
“…Therefore, in pharmacogenomics greater emphasis may have to be placed on functional validation of GWAS “signals” and on biological plausibility. Additionally, one must recognize that the larger the sample size, the more likely that features which confound the genotype/phenotype relationship will be undocumented or uncontrolled, thus diluting the “purity” of the phenotype and potentially reducing power [25]. …”
Section: Considerationsmentioning
confidence: 99%
“…While our focus has been on Crohn’s disease, the presented methodology can be applied to any complex heterogeneous disease. Furthermore, our aim was to explore phenotypic variability by relating the detected genetic-based groups to clinical subphenotypes, but Thornton-Wells et al [40] and Thornton-Wells et al [11] suggested using cluster analysis to unravel various other forms of heterogeneity, e.g., trait heterogeneity and genetic heterogeneity as well. Thus, the presented methodology to correct for population stratification in cluster analysis of SNP data might also prove useful for detection of other factors of heterogeneity in complex human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Cluster analysis of individuals based on SNPs has been performed with different purposes, e.g., the detection of genetic-based patient groups, the dissection of trait heterogeneity or the identification of disease susceptible SNPs [9,11-13]. To our knowledge, confounding by population stratification has largely been neglected in any of these analyses.…”
Section: Introductionmentioning
confidence: 99%
“…For example, genetic heterogeneity, or more specifically either locus or allelic heterogeneity, refers to different patterns of genetic variant associations within different subject groups (Thornton-Wells, Moore, & Haines, 2004;Urbanowicz, Andrew, Karagas, & Moore, 2013). The term "heterogeneity" has a variety of contextual meanings.…”
Section: Introductionmentioning
confidence: 99%